MODERASI BERAGAMA BERBASIS TRADISI PESANTREN PADA MA’HAD ALY AS’ADIYAH SENGKANG WAJO SULAWESI SELATAN - Saddam; Andi EKi (Harmoni, 2021)
Radicalism religion has entered into various sectors of life, including in the realm of education. For this reason, Pesantren as the center of Islamic Education must take a role in the mainstreaming of ideas and moderate attitudes in religion that is in accordance with the noble values of Islam that is peace. In this paper, religious moderation in Ma’had Aly As’adiyah Sengkang will be explored. This paper uses field research which is included in the type of qualitative research using descriptive methods.In this research, it is found that the values of religious moderation in Ma’had Aly As’adiyah; Tawassuth tawazun, I’tidal (fair), tasamuh (tolerance), musawah, Syura, ishlah, aulawiyah, tatawwur wa ibtikar (dynamic and innovative), tahaddur (civilized), wathaniyah wa muwathanah, qudwatiyah. The inculcation of Religious moderation values in Ma’had Aly As’adiyah is carried out by several methods, namely formal classes, halaqah or mappesantreng methods.